2021
DOI: 10.3390/ijms22168734
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Lipidomic Approach for Mapping and Exploring the Molecular Networks Underlying Physical Exercise: A Systematic Review

Abstract: Maintaining appropriate levels of physical exercise is an optimal way for keeping a good state of health. At the same time, optimal exercise performance necessitates an integrated organ system response. In this respect, physical exercise has numerous repercussions on metabolism and function of different organs and tissues by enhancing whole-body metabolic homeostasis in response to different exercise-related adaptations. Specifically, both prolonged and intensive physical exercise produce vast changes in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Physical exercise has numerous repercussions on metabolism and function of different organs and tissues by enhancing whole-body metabolic homeostasis in response to different exercise-related adaptations. In a review, Latino et al showed as exercise determine significant changes in lipidomic profiles, but they manifested in very different ways depending on the type of tissue examined ( 52 ) As healthy lifestyle during pubertal years is highly related to accelerated biological maturation in childhood and adolescence ( 53 , 54 ), its recommended to consider it in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has numerous repercussions on metabolism and function of different organs and tissues by enhancing whole-body metabolic homeostasis in response to different exercise-related adaptations. In a review, Latino et al showed as exercise determine significant changes in lipidomic profiles, but they manifested in very different ways depending on the type of tissue examined ( 52 ) As healthy lifestyle during pubertal years is highly related to accelerated biological maturation in childhood and adolescence ( 53 , 54 ), its recommended to consider it in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring was performed independently by the four aforementioned investigators. The modified Jadad score ranges from 0 to 5, and each question has a dichotomous answer (yes: 1 point; no: 0 points) [30,31]. A higher score indicates better RCT quality.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The applied methodological approaches of modern‐age lipidomics help differentiate between lipid classes and, in some cases, are specific enough to identify lipid chain structures including double bonding and side chain locations which may be important to classify the source of the lipid or the biological process in which it was synthesized. This allows researchers to study the flux of complex biological systems more appropriately to further understand the metabolic impact of exercise across varied populations 102 . Lipidomics remains an emerging method within SES research but, nonetheless, is providing data to improve the general understanding of lipid metabolism in exercise‐based scenarios.…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
“…This allows researchers to study the flux of complex biological systems more appropriately to further understand the metabolic impact of exercise across varied populations. 102 Lipidomics remains an emerging method within SES research but, nonetheless, is providing data to improve the general understanding of lipid metabolism in exercise‐based scenarios.…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%